2011
DOI: 10.1038/oby.2010.148
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Intramyocellular Lipid to Insulin Sensitivity May Differ With Ethnicity in Healthy Girls and Women

Abstract: The prevalence of type 2 diabetes is greater among African Americans (AA) vs. European Americans (EA), independent of obesity and lifestyle. We tested the hypothesis that intramyocellular lipid (IMCL) or extramycellular lipid (EMCL) would be associated with insulin sensitivity among healthy young women, and that the associations would differ with ethnic background. We also explored the hypothesis that adipokines and estradiol would be associated with muscle lipid content. Participants were 57 healthy, normogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…One possible explanation for the disparity within nonobese subjects is a differential β-cell function between race/ethnicity groups. Results from clinical studies have shown decreased insulin sensitivity in African American women compared with European American women (28,29), with differential responses by race/ethnicity in insulin sensitivity and β-cell responsiveness according to level of body fat (30) and location of body fat depots (31,32). Although obesity alone causes a state of insulin resistance, it is possible that the pancreatic response is different in the presence of adipose tissue within different race/ethnicity groups, which may help to explain our observation by BMI category.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the disparity within nonobese subjects is a differential β-cell function between race/ethnicity groups. Results from clinical studies have shown decreased insulin sensitivity in African American women compared with European American women (28,29), with differential responses by race/ethnicity in insulin sensitivity and β-cell responsiveness according to level of body fat (30) and location of body fat depots (31,32). Although obesity alone causes a state of insulin resistance, it is possible that the pancreatic response is different in the presence of adipose tissue within different race/ethnicity groups, which may help to explain our observation by BMI category.…”
Section: Discussionmentioning
confidence: 99%
“…However, when MRS has been used to quantify both intramyocellular (IMCL) and extramyocellular lipid (IMCL) content, only EMCL [81], and not IMCL [56, 81], was increased in African American and black South Africans (Goedecke et al, unpublished). Further, IMCL was associated with insulin sensitivity in white, but not black women and girls [81]. …”
Section: Ectopic Fat Depositionmentioning
confidence: 99%
“…Lipid accumulation within muscle cells (intramyocellular lipid, IMCL) is associated with insulin resistance in obesity and T2DM [24]. Racial differences in insulin sensitivity have been noted in adults [5, 6] and children [7, 8], such that African-Americans have lower insulin sensitivity than their Caucasian peers despite similar BMI or total fat. IMCL is an ectopic fat depot that may in part explain the racial differences in insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%